The Influence of Fiscal Decentralization of Economic Growth in Nias Islands - Telaumbanua, Ya'aman; Sirojuzilam, Sirojuzilam (International Journal Labs, 2023)
In general, the fiscal decentralization policy has succeeded in reducing fiscal disparities between levels of government and between regions, as well as encouraging improvements in public services and competitiveness in the regions. Increasing regional revenues from balancing funds, the authority to determine expenditure allocations and the superiority of the position of regional governments that are closer to the people are able to increase economic efficiency and allocate more priority spending according to community needs. However, the conditions of each region in Indonesia vary greatly, so that the impact of fiscal decentralization policies on regional economic growth also varies. On this occasion, research was conducted to analyze the effect of fiscal decentralization on the economic growth of the Nias Islands. Fiscal decentralization analysis uses income indicators, expenditure indicators and autonomy indicators and includes the population growth factor as a control variable. This study uses panel data from five districts/cities in the Nias Islands during the 2010-2021 period using the Fixed Effect Model method. Based on the results of panel data estimation in this study, the results show that fiscal decentralization has proven to have a significant effect on economic growth in the Nias Islands.